Forêt et biodiversité des zones humides en France : Quelles relations ? Quelles perspectives pour l’avenir ? - Yves Petit-Berghem (VertigO)
In France, many humid zones have benefited from forestation policies, initiated as early as the XIXth century. Forestation has provided impetus to new territorial dynamics, and enables these humid zones to be improved by capitalising on a resource, which is exploited many years later. Indeed, the economic context today is no longer what it was in the past, and the forester keeper’s mission is no longer necessarily that of producing wood. The regulatory context (laws, circulars, international directives) favours an improved allowance for biological diversity in the development and management of forests. This new context has transcribed major evolutions in thinking and behaviour into law, following significant transformations in the knowledge and understanding of forester keepers. Today, the service rendered by the forests is recognised. In many humid zones, the forest thus contributes both by protecting an exceptional environment (habitats), and by supplying water of a very high quality. However, the services rendered also have a cost, which leads to new controversies between those responsible for the forests and for water.